An antioxidant role for calcium antagonists in the prevention of adrenaline mediated myocardial and endothelial damage. Issue 6 (June 1991) - Noronha-Dutra, A A; Steen-Dutra, E M; Woolf, N
Abstract : OBJECTIVE--To investigate the mechanism of calcium antagonist mediated cytoprotection against the damaging effects of adrenaline in vivo on cardiac myocytes and human endothelial cells from the umbilical vein. METHODS--Human endothelial cells cultured from the umbilical vein and isolated rat cardiac myocytes were treated with plasma from rats given adrenaline 30 minutes previously with pretreatment with calcium antagonists and without. The effect on indices of cell damage that suggest oxidation stress was determined. RESULTS--Pretreatment of rats with calcium antagonists before adrenaline administration largely inhibited the cytotoxic effects of their plasma on the two target cells used. Plasma taken from animals not pretreated with calcium antagonists caused release of oxidised glutathione from cells, a fall in intra-cellular reduced glutathione concentration, a fall in ATP production, and release of angiotensin converting enzyme from the endothelial cells. CONCLUSION--Calcium antagonists protect against the cardiotoxic effects of catecholamine by preventing the generation of plasma borne cytotoxic compounds, which are probably free radicals.